Handling Money: Renter's Insurance - Mary N. Harrison (EDIS)
Everyone renting an apartment or a house should have renter's insurance. It will protect you against losses from disasters such as hurricanes and fire. This document is FCS5235-03, one of a series of the Department of Family, Youth and Community Sciences, UF/IFAS Extension. Original publication date: May 2002. Revised: December 2005.